Endocrine Dysfunction in Traumatic Subarachnoid Hemorrhage: A Prospective Study - Pankaj Gupta; Radheyshyam S. Mittal; Achal Sharma; Varsha Kumar (Indian Journal of Neurosurgery)
Background This study has prospectively investigated pituitary function and their correlation with severity, pressure effect, and Glasgow outcome scale in the acute phase of traumatic subarachnoid hemorrhage (SAH). Most of the retrospective studies have demonstrated that traumatic SAH-mediated hypopituitarism could be more frequent than previously known. Objectives The aim of the study is to find the prevalence of endocrine dysfunction in traumatic SAH and its correlation with severity of injury and final outcome. Materials and Methods Eighty-four consecutive patients of traumatic SAH formed the study group. Apart from clinical assessment, noncontrast computed tomography of the head was performed on all patients on admission. The hormonal analysis (FT3, FT4, thyroid-stimulating hormone, growth hormone [GH], cortisol, prolactin, testosterone) was performed within 24 hours of traumatic brain injury and was repeated on the seventh day amongst the patients who survived. Results Most common hormone to increase on day one was cortisol (48.78%), while on day seven follicle-stimulating hormones and cortisol (15.38%) showed increment in levels. Most common hormone to decrease on day one was FT3 (36.84%) and GH (36.26%), while on day seven testosterone (66.67%) and FT4 (30.76%) showed decreasing levels. Hormone most resistant to change was prolactin. Conclusion Hormonal dysfunction is common in moderate to severe traumatic brain injury. There is a direct association between radiological grading (Fischer) of SAH and hormonal profile changes. Performance of hormonal analysis should be considered in patients with moderate to severe traumatic brain injury, preferably with high-grade SAH, so that appropriate hormonal replacement can be done to optimize the clinical outcome.